PERBANDINGAN NILAI BUDAYA DALAM DONGENG JEPANG DAN DONGENG BALI - Ida Bagus Gede, Candra Prayoga (Humanis, 2015)
Cultural values are the basic concept that is very important for people's lives. Cultural values are also considered good by a group of people because they give the characteristics of the community. This study discusses the comparison of the value of culture in Japanese folktales and Bali nese folktales . The method used in this study is a literature and informal method. The theory used are the theory of comparative literature proposed by Damono and cultural value theory proposed by Kluckhonh. The analysis shows the similarities and differences in terms of cultural values between these folktales. The similarities are in (1) a belief system of religion, (2) a sense of loving for animals and plants , (3) the concept of indebtedness in Japanese and Balinese folktales. The difference is about (1) the nam ing system of Japanese and Balinese people, (2) the differentiate of the season make a difference culture calues between Japan and Bali.
Keywords: cultural, comparative literature, Folktales